Simulation and Experimental Verification of Electrical Power Output of a Microcontroller Based Solar Tracking Photovoltaic Module - Adewole, Bamiji Z; Malomo, Babafemi O; Olatunji, Oluwaseun P; Ikobayo, Abiodun O (International Journal of Sustainable Energy and Environmental Research, 2020)
The study evaluated the performance of a microcontroller based solar tracking PV system. The system utilized a stepper motor, two light dependent resistors and a worm gear to intelligently control the rotation of the photovoltaic modules such that it automatically provides the best alignment of the solar panel with the sun for maximum power output. The performance of the PV system was evaluated through simulation and experiment. The effect of different levels of solar irradiance and cell temperature was investigated on the power output of the solar tracking PV system. An increase in maximum power output (Pmax, m), actual light generated current (Ipv) and actual short circuit current (Isc) has been observed with the increase in solar irradiance. With the decreasing cell temperature, the power produced decreases. The percentage relative error between the optimum simulated and the experimental values for Pmax and Ipv was found below 5%, indicating that the simulation model found good agreement with the experimental values. The results are expected to provide insights into the interaction between weather data (irradiance and temperature) and PV module power output during conversion of solar energy into electricity.